P(x) делится на Q(x), если существует многочлен R(x) такой, что P(x) = Q(x) * R(x). Если всё так, то по правилам дифференцирования P'(x) = Q'(x) R(x) + Q(x) R'(x).
P(x) делится на Q(x), если существует многочлен R(x) такой, что P(x) = Q(x) * R(x). Если всё так, то по правилам дифференцирования P'(x) = Q'(x) R(x) + Q(x) R'(x).
(3x^2+4)^2+(3x^2-4)^2-2(5-3x^2)(5+3x^2)=9x^4+24x^2+16+9x^4-24x^2+16-2*(5-3x^2)*(5+3x^2)=18x^4+16+16-2*(5-3x^2)*(5+3x^2)=18x^4+32-(10-6x^2)*(5+3x^2)=18x^4+32-50+18x^4=18x^4-18+18x^4=36x^4-18